Inovação no desenvolvimento de produtos em cluster industrial: Práticas do setor moveleiro de votuporanga - Dias, Eliza Cristina; Oprime, Pedro Carlos; Jugend, Daniel [UNESP] (My University, 2013)
It is notorious that the cluster formation is a possibility for micro, small and medium companies to become more competitive. This research therefore aims to analyze leading practices for product innovation in companies belonging to the cluster of Votuporanga, which is the largest furniture industry in production and exporting of São Paulo state. Therefore, we conducted a survey research and data were collected from 61 furniture companies in the region of Votuporanga-SP. Among the main results it is observed that the incremental innovation of products is a central characteristic between the companies in cluster and there is little collaboration for the joint development of products from these companies with external agents such as research institutes, universities and even suppliers.
Innovation in product development in industrial clusters: Practices of the votuporanga furniture industry
Keywords: Cluster; Innovation; Product development